ELISA tests for dapsone and pyrimethamine and their application in a malaria chemoprophylaxis programme. - Greenwood, B; Greenwood, A; Bradley, A; Shenton, F; Smith, A; Snow, R; Williams, K; Eggelte, T; Huikeshoven, H; de Wit, M (1986)
Enzyme-linked immunosorbent asays (ELISAs) are described for determining levels of dapsone and pyrimethamine in urine. Both assays have a sensitivity of about 20 mug/l and are reproducible, but each produces some false positives. The problem of false positive reactions was partially obviated by requiring positive results in both assays. In a pilot study involving 50 children aged 3 months to 4 years who were given a single dose of Maloprim (pyrimethamine + dapsone), 75% were positive for dapsone 7 days after administration of the drug, while 25% were still positive 15 days after its administration. The corresponding proportions for pyrimethamine were 73% and 30%, respectively. Comparison of the results obtained in a larger chemoprophylaxis trial with those from the pilot study indicated that the assays described could be used to investigate whether antimalarials had been taken.